Use of templates and self-tapping metal screws for temporary fixation of a resorbable plate system - Sukegawa, Shintaro (Ann Maxillofac Surg, 2015)
Resorbable plate systems combine the benefits of rigid internal fixation with the convenience of biodegradation; thus, precluding the need for removal and reducing their interference with craniofacial growth. However, in surgeries involving maxillofacial bone, when reduction or repositioning of the bone segment is inaccurate, refixation and rebending of the plate may be necessary. Here, we report using a temporary plate with self-tapping metal screws to avoid repeated rebending of the resorbable plate and using additional screws following inaccurate fixation in maxillofacial surgeries.